1999
DOI: 10.1093/glycob/9.11.1281
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the acid-labile component of Candida albicans mannan from hydrophobic and hydrophilic yeast cells

Abstract: Cell surface hydrophobicity of the opportunistic fungal pathogen Candida albicans has been linked to the level of cell wall protein glycosylation. Previous work demonstrated that outer chain mannosylation, rather than overall glycosylation, correlated with cell surface hydrophobicity. These studies further suggested that the phosphodiester-linked, acid-labile beta-1,2-mannan was the correlating element. The present work tests this hypothesis and extends the previous results. The composition of bulk mannan from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 26 publications
4
41
1
Order By: Relevance
“…These studies implicated the protein recognized by MAb and perhaps the hydrophobic properties in the adherence of ligands and cells. The acid-released fraction of mannan from hydrophobic cells was longer and more abundant than that from hydrophilic cells (236), and hydrophobicity was independent of serotype A or B (235).…”
Section: Adhesinsmentioning
confidence: 89%
“…These studies implicated the protein recognized by MAb and perhaps the hydrophobic properties in the adherence of ligands and cells. The acid-released fraction of mannan from hydrophobic cells was longer and more abundant than that from hydrophilic cells (236), and hydrophobicity was independent of serotype A or B (235).…”
Section: Adhesinsmentioning
confidence: 89%
“…Jabra-Rizk et al recently reported that the surface fibrils of C. dubliniensis do not vary in architecture between cells grown at 25 and 37°C and that the fibrils resemble those seen on hydrophobic C. albicans cells (27,36). The mannosylation modification that appears primarily responsible for the change in the C. albicans N-glycan chain involves the acid labile ␤-1,2-oligomannoside group (41,42). Here we report that C. dubliniensis differs from C. albicans in its ability to express CSH and in its CSH-related glycoprotein components.…”
mentioning
confidence: 79%
“…Cell wall glycans of C. albicans LGH1095 and C. dubliniensis CD36 were isolated and separated into mannan and glucan fractions as described previously (41,42). Briefly, cells are grown to stationary phase (26 h; third transfer) and washed and the cell pellet is dried.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations